1998
DOI: 10.1038/24179
|View full text |Cite
|
Sign up to set email alerts
|

The murine gene p27Kip1 is haplo-insufficient for tumour suppression

Abstract: Abstractp27 Kip1 is a candidate human tumour-suppressor protein, because it is able to inhibit cyclindependent kinases and block cell proliferation [1][2][3][4][5] . Abnormally low levels of the p27 protein are frequently found in human carcinomas, and these low levels correlate directly with both histological aggressiveness and patient mortality [6][7][8][9][10] . However, it has not been possible to establish a causal link between p27 and tumour suppression, because only rare instances of homozygous inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
530
5
10

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(571 citation statements)
references
References 24 publications
26
530
5
10
Order By: Relevance
“…Alterations in p27 Kip1 warrant particular attention as p27 Kip1 protein levels are reduced in several types of cancer including melanoma (Catzavelos et al, 1997;Loda et al, 1997;Mori et al, 1997;Florenes et al, 1998;Kawana et al, 1998), and p27 Kip1 heterozygous mice are prone to induced tumor formation (Fero et al, 1998). B-RAF is mutated in approximately 70% of melanomas (Davies et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in p27 Kip1 warrant particular attention as p27 Kip1 protein levels are reduced in several types of cancer including melanoma (Catzavelos et al, 1997;Loda et al, 1997;Mori et al, 1997;Florenes et al, 1998;Kawana et al, 1998), and p27 Kip1 heterozygous mice are prone to induced tumor formation (Fero et al, 1998). B-RAF is mutated in approximately 70% of melanomas (Davies et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…When Rb +/− and p27 −/− are crossed, Rb +/− and p27 −/− offspring develop more aggressive tumors and at an earlier age than Rb +/− alone, indicating that Rb and p27 cooperate in tumor suppression [33]. p27 is classified as a haploinsufficient tumor suppressor because mutation in just one allele of Cdkn1b, the gene encoding mouse p27, renders mice more susceptible to tumorigenesis by DNA-damaging agents compared to wild-type mice [34]. Furthermore, concomitant inactivation of one allele of the tumor suppressor gene Pten and both or even one of the Cdkn1b alleles accelerates spontaneous neoplastic transformation and incidence of tumors of various histological origins [35].…”
Section: P27 As a Tumor Suppressor In Mouse Modelsmentioning
confidence: 99%
“…In contrast to the tumorigenic e ect of p27-de®ciency on intermediate lobe cells, hyperplasia of the spleen, thymus, testis and ovary does not progress to neoplasia under controlled environmental conditions. However, Fero and coworkers (Fero et al, 1998) recently reported that p27+/7 mice, as well as p277/7 mice, are more susceptible than are p27+/+ mice to both radiationand chemical-induced tumors of the lung, ovary and endometrium. These results indicate that a partial reduction in p27 can sensitize cells, in a tissue-speci®c manner, to external tumorigenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that a partial reduction in p27 can sensitize cells, in a tissue-speci®c manner, to external tumorigenic factors. Therefore, p27 is considered haplo-insu cient for tumor suppression (Fero et al, 1998).…”
Section: Introductionmentioning
confidence: 99%